Big Daddy Frederick G. Gardiner and the Building of Metropolitan Toronto - Colton, Timothy (University of Toronto Press, 2017)
Frederick Gardiner's public life was rich and long, from his initiation into politics as a Toronto schoolboy before the First World War, through his involvement with the Ontario Conservative party and suburban politics in the 1930s and 1940s, on through his years as first chairman of Metropolitan Toronto (1953-61), to the relinquishing of his last public office in 1979. This is a readable and perceptive biography of the exuberant and powerful politician who captured the public imagination of Toronto and created a legend around himself during his lifetime. The book focuses mainly on Gardiner's experience as founding boss of Metropolitan Toronto. This first metropolitan government in North America was in many ways his personal machine. Gardiner made an indispensable contribution to its effectiveness and to its very survival. He presided over an unprecedented boom in urban development and construction.